Impact cratering on porous targets in the strength regime. (1st December 2017) - Nakamura, Akiko M.
Abstract: Cratering on small bodies is crucial for the collision cascade and also contributes to the ejection of dust particles into interplanetary space. A crater cavity forms against the mechanical strength of the surface, gravitational acceleration, or both. The formation of moderately sized craters that are sufficiently larger than the thickness of the regolith on small bodies, in which mechanical strength plays the dominant role rather than gravitational acceleration, is in the strength regime. The formation of microcraters on blocks on the surface is also within the strength regime. On the other hand, the formation of a crater of a size comparable to the thickness of the regolith is affected by both gravitational acceleration and cohesion between regolith particles. In this short review, we compile data from the literature pertaining to impact cratering experiments on porous targets, and summarize the ratio of spall diameter to pit diameter, the depth, diameter, and volume of the crater cavity, and the ratio of depth to diameter. Among targets with various porosities studied in the laboratory to date, based on conventional scaling laws (Holsapple and Schmidt, J. Geophys. Res., 87, 1849–1870, 1982) the cratering efficiency obtained for porous sedimentary rocks (Suzuki et al., J. Geophys. Res. 117, E08012, 2012) is intermediate. A comparison with microcraters formed on a glass target with impact velocities up to 14 km s −1 indicates a different dependence of cratering efficiency and depth-to-diameter ratio on impact velocity.